- Tim x
\(2^x.2^{x+1}.2^{x+2}......2^{x+100}=2^{5555}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1,\) thiếu đề
\(2,\dfrac{5x+2}{6}-\dfrac{8x-1}{3}=\dfrac{4x+2}{5}-5\)
\(\Leftrightarrow\dfrac{5\left(5x+2\right)}{30}-\dfrac{10\left(8x-1\right)}{30}=\dfrac{6\left(4x+2\right)}{30}-\dfrac{150}{30}\)
\(\Leftrightarrow5\left(5x+2\right)-10\left(8x-1\right)=6\left(4x+2\right)-150\)
\(\Leftrightarrow25x+10-80x+10=24x+12-150\)
\(\Leftrightarrow-55x+20=24x-138\)
\(\Leftrightarrow24x-138+55x-20=0\)
\(\Leftrightarrow79x-158=0\)
\(\Leftrightarrow x=2\)
\(3,ĐKXĐ:\left\{{}\begin{matrix}x\ne1\\x\ne-1\\x\ne3\end{matrix}\right.\\ \dfrac{x}{2x-6}+\dfrac{x}{2x-2}=\dfrac{-2x}{\left(x+1\right)\left(3-x\right)}\)
\(\Leftrightarrow\dfrac{x}{2\left(x-3\right)}+\dfrac{x}{2\left(x-1\right)}+\dfrac{2x}{\left(x+1\right)\left(3-x\right)}=0\)
\(\Leftrightarrow\dfrac{x}{2\left(x-3\right)}+\dfrac{x}{2\left(x-1\right)}-\dfrac{2x}{\left(x+1\right)\left(x-3\right)}=0\)
\(\Leftrightarrow x\left(\dfrac{1}{2\left(x-3\right)}+\dfrac{1}{2\left(x-1\right)}-\dfrac{2}{\left(x+1\right)\left(x-3\right)}\right)=0\)
\(\Leftrightarrow x\left(\dfrac{\left(x-1\right)\left(x+1\right)}{2\left(x-1\right)\left(x-3\right)\left(x+1\right)}+\dfrac{\left(x-3\right)\left(x+1\right)}{2\left(x-1\right)\left(x-3\right)\left(x+1\right)}-\dfrac{4\left(x-1\right)}{2\left(x+1\right)\left(x-3\right)\left(x-1\right)}\right)=0\)
\(\Leftrightarrow x\left(\dfrac{x^2-1}{2\left(x-1\right)\left(x-3\right)\left(x+1\right)}+\dfrac{x^2-2x-3}{2\left(x-1\right)\left(x-3\right)\left(x+1\right)}-\dfrac{4x-4}{2\left(x+1\right)\left(x-3\right)\left(x-1\right)}\right)=0\)
\(\Leftrightarrow x.\dfrac{x^2-1+x^2-2x-3-4x+4}{2\left(x-1\right)\left(x-3\right)\left(x+1\right)}=0\)
\(\Leftrightarrow x.\dfrac{2x^2-6x}{2\left(x-1\right)\left(x-3\right)\left(x+1\right)}=0\)
\(\Leftrightarrow x.\dfrac{2x\left(x-3\right)}{2\left(x-1\right)\left(x-3\right)\left(x+1\right)}=0\)
\(\Leftrightarrow x.\dfrac{x}{\left(x-1\right)\left(x+1\right)}=0\)
\(\Leftrightarrow\dfrac{x^2}{\left(x-1\right)\left(x+1\right)}=0\)
\(\Leftrightarrow x=0\)
\(\left(2x-3\right)^{10x}=\left(3-2x\right)^{100}\)
\(\Leftrightarrow\left(2x-3\right)^{10x}=\left(2x-3\right)^{100}\)
\(\Leftrightarrow10x=100\Leftrightarrow x=100:10=10\)
1. \(2x< -6\Leftrightarrow x< \dfrac{-6}{2}\Leftrightarrow x< -3\)
2. \(x-3>0\Leftrightarrow x>0+3\Leftrightarrow x>3\)
3. \(x+4>2x+3\Leftrightarrow4-3>2x-x\Leftrightarrow x< 1\)
4. \(-3x\le0\Leftrightarrow x\ge0\cdot\left(-\dfrac{1}{3}\right)\Leftrightarrow x\ge0\)
\(\Leftrightarrow\left(2x+3-2x+5\right)^2=x^2+6x+64\)
=>x^2+6x=0
=>x(x+6)=0
=>x=0 hoặc x=-6
\(\left(2x-1\right)^2=100\\ \Leftrightarrow\left(2x-1\right)^2=\pm10^2\\ \Rightarrow\left[{}\begin{matrix}2x-1=10\\2x-1=-10\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}2x=11\\2x=-9\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=5,5\\x=-4,5\end{matrix}\right.\)
Vậy \(x=5,5\) hoặc \(x=-4,5\)
cậu gửi lời mời kp vs mk nha